Alakuoren ksenoliitit Kaavi-Kuopio-alueen Lahtojoen kimberliitissä - Järvinen, Ville (Helsingfors universitet, 2015)
Five granulite xenoliths entrained in the ~600 Ma Lahtojoki kimberlite pipe in eastern Finland represent the lower crust below the suture zone between the Archaean Karelian craton and the Paleoproterozoic Svecofennian terranes. They provide direct information on the petrology of the lower cratonic crust, and the processes that controlled its evolution. Studied xenoliths comprise a dry intermediate garnet granulite, three mafic garnet granulites with amphibole contents ranging from 3–50 vol–%, and a peraluminous micaceous garnet gneiss. Granulites have granoblastic fabrics with mineral assemblage Grt – Cpx – Plg ± Amb ± Qtz ± Ilm ± Rt ± Bt, with pink garnet and green clinopyroxene. Gneiss is coarse grained with a heavily deformed and strained fabric with mineral assemblage Qzt – Bt – Grt – Sil. Mineral chemistry based TWEEQU–thermobarometry indicates equilibration of mafic granulites at ca. 800 °C and 9.5–10.5 kbar and intermediate granulite at ca 800 °C and 17.5 kbar. The pressure estimates correspond to crustal depths of 38–55 km. Equilibration temperature for garnet gneiss is ca. 700 °C – TWEEQU based pressure estimate was not possible, but based on Grt–Sil stability equilibration pressure can be constrained to ca. 4–8.5 kbar. Mineral zonation indicates slight post peak cooling and decompression of some samples. Whole-rock geochemical composition (major and trace elements) implies derivation of dry (<10 vol–% Amb) mafic granulite from a Ni-Cr fractionated basaltic melt. Enrichment in LREE and other trace elements suggests a low to moderate degree of melting of a primitive mantle source. The sample could represent a mafic underplate crystallized in situ. Amphibole and enrichment in K and Rb could indicate a later metasomatic enrichment event. The intermediate granulite is anomalous in composition compared to other Kaavi-Kuopio lower crustal xenoliths. REE composition, depletion in K, Rb, Zr, Hf, Nb, Ta, and strong enrichment in Sr and a prominent positive Eu anomaly imply that the sample represents a ...